Crackingchambers Coffee Shop Marketing Communication Strategy Analysis: Analisis Strategi Komunikasi Pemasaran Crackingchambers Coffee Shop - Miftachul Jannah; Poppy Febriana (Academia Open, 2024)
This study investigates the marketing communication strategy employed by a coffee shop in a competitive culinary landscape, focusing on attracting consumer interest in Sidoarjo. Utilizing descriptive qualitative research, the study employs interviews and observations to analyze data, employing techniques such as personal selling, sales promotions, and digital platforms for publicity. Results reveal that the coffee shop successfully engages in events, utilizes social media platforms, and leverages delivery services to maintain a competitive edge. The findings shed light on effective strategies for businesses navigating the intense competition within the coffee industry, providing valuable insights for practitioners and researchers alike. Highlights : Strategic Differentiation: Examining how coffee shops employ marketing communication strategies to stand out in a saturated culinary market. Digital Engagement: Investigating the role of social media platforms and delivery services in enhancing visibility and consumer interest. Competitive Survival: Highlighting effective tactics, such as personal selling and sales promotions, to thrive in the fierce competition within the coffee industry. Keywords: Coffee industry, Marketing communication, Consumer attraction, Culinary competition, Digital platforms